Hydroxyapatite and cobalt ferrite composites as ciprofloxacin release systems for the treatment of osteomyelitis – An experimental study - Cristiane Carneiro Vital Cintra; Dayana Alersa Ferreira Ermita; Gabriela Castro Lopes Evangelista; Rafael Colman Cardoso; Rodrigo Viana Sepúlveda; Emily Correna Carlo Reis; Fabrício LucianiValente; Carlos Eduardo Pereira; Raffaella Bertoni Cavalcanti Teixeira Santos; Andréa Pacheco Batista Borges (The Veterinary Journal, 2026)

Corn oil-formulated Cordyceps javanica: a high-performance, low-impact tool for integrated tick management - Joana da Rocha Matos; Adriani da Silva Carneiro; Thaís Almeida Corrêa; Emily Mesquita; Laura Nobrega Meirelles; Victória Silvestre Bório; Américo de Castro Monteiro-Sobrinho; Tadeu Augusto van Tol de Castro; Andrés Calderín García; Mariana Guedes Camargo; Isabele da Costa Angelo; José Francisco Arruda e Silva; et al. (Experimental and Applied Acarology, 2026)
Mycoacaricides represent a promising alternative for managing resistant tick populations. This study evaluated the efficacy of corn oil–based Cordyceps javanica formulations against non-parasitic stages the southern cattle tick Rhipicephalus microplus under laboratory and semi-field conditions. Additionally, fungal persistence in soil and possible alterations in soil composition were assessed using ATR-FTIR spectroscopy combined with chemometric analysis. Corn oil (1%, 3%, and 5%) combined with 0.01% silicone oil did not affect conidial germination (> 98.4%). Corn oil and C. javanica suspensions alone yielded larval average mortality of 20.1% and 18.8%, respectively, 15 days after the treatment. When formulated in corn oil, averages of larval mortality ranging from 64.1% on day 5 to 100% on day 15, indicating a synergistic effect between fungus and oil. Corn oil alone resulted in a female tick control percent ranged from 20.5 to 73.3%, while the fungus alone achieved 28.2% and 14.9% control at 10⁷ and 10⁸ conidia/mL, respectively. All fungus–oil formulations significantly reduced female reproductive efficiency, achieving 90–100% tick control. Under semi-field conditions, the 10⁸ conidia/mL + 3% corn oil formulation reduced larval recovery from Urochloa decumbens pots by 98.6% compared to the oil and silicone control. Thirty days after application, C. javanica persisted in soil at 2.1 ± 0.3 × 10⁵ CFU/g (39.4% recovery). ATR-FTIR analysis showed no detectable alterations in the soil’s chemical profile following application of any formulation. These results highlight the potential of oil-based C. javanica formulations as an effective and sustainable tool for integrated tick management in livestock systems.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Enterolignans: from natural origins to cardiometabolic significance, including chemistry, dietary sources, bioavailability, and activity - Emily P. Laveriano-Santos; Carlos Luque-Corredera; Marta Trius-Soler; Julian Lozano-Castellón; Inés Dominguez-López; Sara Castro-Barquero; Anna Vallverdú-Queralt; Rosa M. Lamuela-Raventós; Maria Pérez (Critical Reviews in Food Science and Nutrition, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Characterization and processing of kaolin from southern Brazil for potential strategic application in the porcelain stoneware tiles manufacturing - André Biava Comin; Alexandre Zaccaron; Emily Saviatto; Juliana Acordi; Fabiano Raupp-Pereira; João Carlos de Castro Abrantes; Manuel Joaquim Ribeiro; Guilherme Silva de Souza (Journal of South American Earth Sciences, 2024)

Detection of Brucella S19 Vaccine Strain DNA in Domestic and Wild Ungulates from Brazilian Pantanal - Gabriel Carvalho de Macedo; Carolina Santos Pereira Cardoso Trindade; Caroline Paes dos Santos; Luiz Gustavo Rodrigues Oliveira Santos; Filipe Martins Santos; William Oliveira de Assis; Alinne Pereira de Castro; Emily Rebeca Antunes Gonçalves; Sávio Freire Bruno; Heitor Miraglia Herrera; Carina Elisei de Oliveira (Current Microbiology, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

A new method for extraction and pre-concentration of the heavy metals using a microemulsion system in winsor II equilibrium and determination by HR-CS AAS - Emily Cintia Tossi de A. Costa; Tereza N. de Castro Dantas; Djalma R. da Silva; Tatiane de A. Maranhão (Chemosphere, 2023)

Bifidobacterium lactis CCT 7858 Improves Gastrointestinal Symptoms by Antibiotics Treatment: a Double-Blind, Randomized, Placebo-Controlled Trial - Monique Michels; Emily Córneo; Luana Cucker; Carla Sasso Simon; Gabriel Fernandes Alves de Jesus; Carolina Michels; Kristian Madeira; Ana Paula Voytena; Marina Rossetto; Fernanda Ramlov; Danusa de Castro Damásio; Felipe Dal-Pizzol (Probiotics and Antimicrobial Proteins, 2023)

Prevalence of Excessive Iodine Intake in Pregnancy and Its Health Consequences: Systematic Review and Meta-analysis - Aline Carare Candido; Almir Antônio Vieira; Emily de Souza Ferreira; Tiago Ricardo Moreira; Sylvia do Carmo Castro Franceschini; Rosângela Minardi Mitre Cotta (Biological Trace Element Research, 2023)

Proximity to residential and workplace pesticides application and the risk of progression of Parkinson's diseases in Central California - Shiwen Li; Beate Ritz; Yufan Gong; Myles Cockburn; Aline Duarte Folle; Irish Del Rosario; Yu Yu; Keren Zhang; Emily Castro; Adrienne M. Keener; Jeff Bronstein; Kimberly C. Paul (Science of The Total Environment, 2023)

Identifying contamination of heavy metals in soils of Peruvian Amazon plain: use of multivariate statistical techniques - José Abel Espinoza-Guillen; Marleni Beatriz Alderete-Malpartida; Jessica Emily Escobar-Mendoza; Ursula Fiorela Navarro-Abarca; Katya Angelot Silva-Castro; Paula Leonor Martinez-Mercado (Environmental Monitoring and Assessment, 2022)

Habitat and Marine Reserve Status Drive Reef Fish Biomass and Functional Diversity in the Largest South Atlantic Coral Reef System (Abrolhos, Brazil) - Fernanda Andreoli Rolim; Tim Langlois; Fábio dos Santos Motta; Guilherme Malagutti de Castro; Emily Lester; Maria Luiza Abieri; Otto Bismarck Fazzano Gadig; Rodrigo Leão de Moura (Frontiers in Marine Science, 2022)
The effects of fishing have been documented across coral reefs worldwide. No-take marine reserves do not only act as a conservation tool but also allow an opportunity to study impacts of fishing, by acting as control sites. In addition, well-planned and well-managed no-take marine reserves (NTRs) provide conservation benefits that are essential to marine biodiversity and ecosystem-based management. The Abrolhos Marine National Park, off the tropical Brazilian coast, protects part of the largest coral reef system in the South Atlantic. To investigate the effects of fishing on reef fish richness, abundance, biomass, and functional diversity of the fish assemblage, we compared sites across two protection levels considering the variation in habitats (Fringing Reefs—Protected; Pinnacles Reefs—Protected; and Coastal Reefs—Open Access), using Baited Remote Underwater Stereo-Video systems (stereo-BRUVs). We adjusted generalized additive mixed models of fish assemblage characteristics with protection levels and environmental variables, such as topographic complexity (mean relief and relief variation), visibility, and benthic cover percentage. Inside NTRs, we found higher total biomass and biomass of fishery target species and carnivores, specifically for the Carcharhinidae (sharks) and Epinephelidae (groupers) families, indicating direct fisheries effects on these groups. In contrast, the ecological parameters of non-target fish were positively correlated with habitat characteristics, including mean relief and variance of relief. Moreover, fish functional diversity was higher within NTRs, demonstrating an even distribution of functional entities. The presence of large mobile predators and the overall higher biomass of carnivores inside the NTR indicate the effect of fishing exclusion. Our results point to the value of NTRs to study the effects of fishing and achieve biodiversity conservation and suggest the importance of using remote sampling methods to assess large mobile predators.

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

B-lymphocyte tolerance and effector function in immunity and autoimmunity - Wasif N. Khan; Jacqueline A. Wright; Eden Kleiman; Justin C. Boucher; Iris Castro; Emily S. Clark (Immunologic Research, 2013)